An exploration of pupils’ and parents’ dissatisfaction with school uniforms in selected secondary schools in Botswana - Erasmus, Alet C. (Aletta Catharina) (University of Pretoria, 2013)
Dissertation (MConsumer Science)--University of Pretoria, 2008.